AB0218 Plasma heparanase levels are elevated in patients with antiphospholipid syndrome and correlate with platelet activation. (23rd January 2014) - Kim, K.-J.; Park, S.-J.; Kim, J.-Y.; Baek, I.-W.; Yoon, C.-H.; Kim, W.-U.; Cho, C.-S.
Abstract : Background: Overexpression of tissue factor (TF) and activation of the coagulation system are characteristic pathophysiology of antiphospholipid syndrome (APS). Heparanase (HPSE) is an endo-b-D-glucuronidase that cleaves heparan sulfate chains on cell surfaces and in the extracellular matrix and is released primarily from activated platelets. It has been reported that non-enzymatic activity of HPSE participates in the regulation of TF gene expression in endothelial cells and its related coagulation pathway. Objectives: To evaluate plasma HPSE concentration and to determine its association with platelet activation in patients with APS Methods: Plasma samples were collected from 19 clinical APS patients with history of thromboembolic events and/or fetal loss, 16 patients only seropositive for antiphospholipid antibodies (aPL), and 10 normal healthy controls. Plasma levels of HPSE, soluble P- and E-selectin were measured by enzyme linked immunosorbent assay. IgG fractions were purified from the sera of 7 APS patients and healthy subjects. Induction of HPSE release from platelets by APS IgG was confirmed by western blot. Results: Plasma HPSE levels were significantly elevated in APS patients compared to controls (1046.8±240.7 vs . 203.6±87.1 mU/ml, P =0.002) and its levels of clinical APS patients were much higher than those of the patients only seropositive for aPL (1326.0±413.1 vs . 695.7±232.2 mU/ml, P =0.02). Plasma HPSE levels were positively correlated with soluble P-selectin levels (r =0.826, P <0.001) but not with soluble E-selectin levels (r =0.186, P =0.307). Moreover, plasma HPSE levels showed a positive correlation with concentration of anti-b2 glycoprotein I antibody in clinical APS patients (r =0.524, P =0.031). Platelets treated with APS IgG in vitro produced significantly larger amount of HPSE in a dose-dependent manner compared with control IgG. Conclusions: Plasma HPSE levels were elevated in patients with APS and correlate with platelet activation, suggesting a potential role of HPSE in prothrombotic state of APS. Disclosure of Interest: None Declared